2022
DOI: 10.1108/bfj-04-2022-0361
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the experiencescape dimensions and customer revisit intentions for specialty urban coffee shops

Abstract: PurposeThe main aim of this research was to explore specialty coffee experience dimensions and what drives revisit intentions through experiencescapes. The theoretical framework on experience co-creation in food and wine consumption by Carvalho et al. (2021) was employed to explore the dimensions of specialty coffee shop experiences and specialty coffee consumer revisit intentions.Design/methodology/approachUsing the interpretivist epistemology, this research explored these factors from the perspectives of cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 86 publications
1
13
0
1
Order By: Relevance
“…This outcome lends greater nuances within contexts of consumption in Samoggia and Riedel's (2018) framework, suggesting the social elements associated with specialty coffee consumption. The findings also alluded to the notion of conspicuous consumption, where participants showed off their experiences at specialty coffee cafes on social networks (Opoku et al, 2023;Xu and Ng, 2023).…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 76%
See 4 more Smart Citations
“…This outcome lends greater nuances within contexts of consumption in Samoggia and Riedel's (2018) framework, suggesting the social elements associated with specialty coffee consumption. The findings also alluded to the notion of conspicuous consumption, where participants showed off their experiences at specialty coffee cafes on social networks (Opoku et al, 2023;Xu and Ng, 2023).…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 76%
“…Just as Spinelli et al (2017) explicate the relevance of coffee in terms of its "social ritual", Opoku et al (2023) found that coffee provides both human-to-human engagement opportunities as well as solo destination experience to consumers. Hence, Opoku et al (2023) echo Richelieu and Korai, (2014) assertion that coffee consumption is underpinned by two modes which are private consumption and its social value of bringing people together. Paradoxically, Opoku et al (2023) and Richelieu and Korai (2014) provide a nuanced understanding of the complexities that surround coffeescape scholarship by unpacking factors that inform its consumption, these studies have their inherent weaknesses in terms of their sample frame and necessitate the need for this current study which specifically target Gen-Z consumers cohort.…”
Section: The Sociocultural Context Of Coffee Consumptionmentioning
confidence: 99%
See 3 more Smart Citations